An upper bound computational model for investigation of fusion effects on adjacent segment biomechanics of the lumbar spine. Issue 14 (26th October 2019) - Zhou, Chaochao; Cha, Thomas; Li, Guoan
Abstract: Prediction of the biomechanical effects of fusion surgery on adjacent segments is a challenge in computational biomechanics of the spine. In this study, a two-segment L3-L4-L5 computational model was developed to simulate the effects of spinal fusion on adjacent segment biomechanical responses under a follower load condition. The interaction between the degenerative segment (L4-5) and the adjacent segment (L3-4) was simulated using an equivalent follower spring. The spring stiffness was calibrated using a rigid fusion of a completely degenerated disc model at the L4-5 level, resulting in an upper bound response at the adjacent (L3-4) segment. The obtained upper bound equivalent follower spring was used to simulate the upper bound biomechanical responses of fusion of the disc with different degeneration grades. It was predicted that as the disc degeneration grade at the degenerative segment decreased, the effect on the adjacent segment responses decreased accordingly after fusion. The data indicated that the upper bound computational model can be a useful computational tool for evaluation of the interaction between segments and for investigation of the biomechanical mechanisms of adjacent segment degeneration after fusion.